Znaczenie kapitału ludzkiego w kreowaniu rozwoju i wzrostu wartości przedsiębiorstwa - Krajewski, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this article is to present two problems determining effective economic activity towards the growth of an enterprise value. These problems indicate: a) human capital creating and multiplying financial and nonfinancial values, b) mutual influence between development and growth from the standpoint of the achieved profit. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 215-221